Nonlinear Finite Element Analysis and Comparison of In-Plane Strength of Circular and Parabolic Arched I-Section Cellular Steel Beam - Besukal Befikadu Zewudie (Advances in Civil Engineering)
The advancement in steel fabrication technology extends the structural and constructional advantages of cellular steel beams into arched cellular steel structure members. However, less attention is given to understanding the in-plane and out-of-plane structural behavior and performance of arched cellular steel beams. This article presents a numerical study using the finite element package ABAQUS to investigate the effect of arch axis geometry (circular and parabolic) and the impact of end support types on the in-plane inelastic buckling strength and buckling mode of I-section arched cellular steel beams. In the nonlinear finite element analysis of the model material nonlinearity, a second-order effect due to large deformation and initial geometric imperfection was incorporated in predicting inelastic buckling load and buckling mode. Furthermore, finite element analysis results were verified by comparing them to the existing experimental work. Test models covering shallow to deep arches of subtended angle in a range of 45–180 were investigated under uniformly distributed vertical loads and mid-span point loads. It was found that nonlinear finite element results fairly replicate the experimental work in predicting inelastic buckling load and post-buckling behavior. From the parametric investigation, it was found that deep parabolic arched cellular steel beams are structurally more efficient than their equivalent circular arched cellular steel beams. Pinned in-plane and free out-of-plane end support conditions result in a reduced inelastic ultimate buckling load capacity of arched cellular steel members when compared to other possible end support types. The geometry of an arch axis has no noticeable impact on the buckling mode of arched cellular steel beams.